Pedagogical strategies and technological solutions to mitigate English public speaking anxiety: A systematic review - Chuanfang, Shi; Asiah, Kassim; Noor Raha, Mohd Radzuan (Asian Scholars Network, 2025)
Public speaking anxiety is a significant barrier to communication and academic achievement among English as a Foreign Language (EFL) and English as a Second Language (ESL) learners. This systematic literature review, adhering to PRISMA guidelines, examines strategies aimed at alleviating this anxiety, with particular attention to the integration of technological innovations. A comprehensive search of databases such as Web of Science, Scopus, and ScienceDirect identified studies published up to 2025 that focused on reducing public speaking anxiety in EFL/ESL learners. The review highlights a range of effective pedagogical strategies, including traditional methods like structured practice, experiential learning approaches that emphasize real-world application, and peer feedback, which fosters a supportive learning environment. Technological tools such as virtual reality (VR) environments, interactive language learning apps, and online platforms are particularly promising. These tools provide immersive, interactive experiences in safe, controlled settings, helping learners build confidence and reduce anxiety. By combining technology with established pedagogical techniques, these approaches address the unique challenges faced by EFL/ESL learners. Future research should focus on assessing the long-term impact of these interventions and exploring emerging technologies to further enhance English public speaking skills and reduce anxiety.